Examining Opportunities and Threats in the Commercialization of Renewable Energy Businesses: A Case Study on Household Consumption - Ghaderi, Zana (Digital Transformation and Administration Innovation, 2024)
The present study investigates the opportunities and threats related to the commercialization of renewable energy businesses with a focus on household consumption. Given the increasing demand for clean energy sources and the limitations of fossil fuel resources, renewable energies—particularly in the residential sector—have emerged as a sustainable solution for energy provision. Utilizing a descriptive-analytical research method, this study identifies and analyzes existing opportunities and threats while also examining the factors influencing the commercialization of such businesses. The findings indicate that declining costs of renewable energy technologies, governmental support, and growing public awareness of the benefits of these sources offer significant opportunities for commercialization. However, challenges such as high initial costs, regulatory complexities, and insufficient public awareness remain as obstacles in this domain. Overall, the commercialization of renewable energy businesses in the household sector requires collaboration and coordination among the government, the private sector, and the community. Addressing these barriers and leveraging existing opportunities are essential for the effective development of these businesses.